Comprehensive geriatric assessment for frail older people in acute hospitals: the HoW-CGA mixed-methods study - Simon Paul Conroy (Health Services and Delivery Research, 2019)
Background: The aim of this study was to provide high-quality evidence on delivering hospital-wide Comprehensive Geriatric Assessment (CGA). Objective(s): (1) To define CGA, its processes, outcomes and costs in the published literature, (2) to identify the processes, outcomes and costs of CGA in existing hospital settings in the UK, (3) to identify the characteristics of the recipients and beneficiaries of CGA in existing hospital settings in the UK and (4) to develop tools that will assist in the implementation of hospital-wide CGA. Design: Mixed-methods study combining a mapping review, national survey, large data analysis and qualitative methods. Participants: People aged ≥ 65 years in acute hospital settings. Data sources: Literature review – Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, MEDLINE and EMBASE. Survey – acute hospital trusts. Large data analyses – (1) people aged ≥ 75 years in 2008 living in Leicester, Nottingham or Southampton (development cohort, n = 22,139); (2) older people admitted for short stay (Nottingham/Leicester, n = 825) to a geriatric ward (Southampton, n = 246) or based in the community (Newcastle, n = 754); (3) people aged ≥ 75 years admitted to acute hospitals in England in 2014–15 (validation study, n = 1,013,590). Toolkit development – multidisciplinary national stakeholder group (co-production); field-testing with cancer/surgical teams in Newcastle/Leicester. Results: Literature search – common outcomes included clinical, operational and destinational, but not patient-reported, outcome measures. Survey – highly variable provision of multidisciplinary assessment and care across hospitals. Quantitative analyses – in the development cohort, older people with frailty diagnoses formed a distinct group and had higher non-elective hospital use than older people without a frailty diagnosis. Patients with the highest 20% of hospital frailty risk scores had increased odds of 30-day mortality [odds ratio (OR) 1.7], long length of stay (OR 6.0) and 30-day re-admission (OR 1.5). The score had moderate agreement with the Fried and Rockwood scales. Pilot toolkit evaluation – participants across sites were still at the beginning of their work to identify patients and plan change. In particular, competing definitions of the role of geriatricians were evident. Limitations: The survey was limited by an incomplete response rate but it still provides the largest description of acute hospital care for older people to date. The risk stratification tool is not contemporaneous, although it remains a powerful predictor of patient harms. The toolkit evaluation is still rather nascent and could have meaningfully continued for another year or more. Conclusions: CGA remains the gold standard approach to improving a range of outcomes for older people in acute hospitals. Older people at risk can be identified using routine hospital data. Toolkits aimed at enhancing the delivery of CGA by non-specialists can be useful but require prolonged geriatrician support and implementation phases. Future work could involve comparing the hospital-based frailty index with the electronic Frailty Index and further testing of the clinical toolkits in specialist services. Funding: The National Institute for Health Research Health Services and Delivery Research programme.